2007
DOI: 10.1002/jctb.1806
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to protein recovery by countercurrent distribution in aqueous two‐phase systems

Abstract: BACKGROUND: The development of efficient processes that will rapidly deliver new biological products to the market is a key goal in biochemical engineering. The establishment of purification processes that permit the recovery of closely related products is essential. The recovery and purification of these types of products is not a trivial task. The current approach exploiting chromatography techniques demands practical alternatives to address the technical and economic constraints. The potential application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Positions of the PEGylated proteins in the chromatogram were associated to the partition behavior of each species in the ATPS (Table ). It has been reported that the increase in the molecular size of the protein diminishes the partition coefficient. The results observed in the chromatogram do not show this particular behavior, this may be attributed to the fact that the di‐PEGylated conjugate has a smaller protein fraction than the mono‐PEGylated protein.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Positions of the PEGylated proteins in the chromatogram were associated to the partition behavior of each species in the ATPS (Table ). It has been reported that the increase in the molecular size of the protein diminishes the partition coefficient. The results observed in the chromatogram do not show this particular behavior, this may be attributed to the fact that the di‐PEGylated conjugate has a smaller protein fraction than the mono‐PEGylated protein.…”
Section: Resultsmentioning
confidence: 99%
“…Positions of the PEGylated proteins in the chromatogram were associated to the partition behavior of each species in the ATPS 29,30 (Table 1). It has been reported 16,27,28 that the increase in the molecular size of the protein diminishes the partition coefficient. The results observed in the chromatogram The molecular mass of the proteins was obtained from references 1, 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations